Cultural Da’wah and Islamic Education Values in Antar Ajong Tradition of People in Melayu Sambas West Kalimantan - Adnan, Adnan; Suriadi, Suriadi; Mujahidin, Mujahidin; Jayadi, Jayadi; Mursidin, Mursidin (Institut Agama Islam Negeri Madura, 2019)
Â This study describes the culture in the tradition of antar ajong in Sambas Regency and also the meaning contained in both cultural preaching and the value of Islamic education. This research is about traditional ritual ceremonies of antar ajong as traditional media in preaching and associating Islamic values. This study uses a qualitative approach. The research aims to describe the antar ajong tradition and the value of Islamic education in antar ajong tradition related to (a) its process of carrying out traditional rituals of antar ajong, (b) the purpose of the antar ajong tradition, (c) the function of the antar ajong ritual as a form of da'wah and as value of Islamic education. The traditional ceremony of antar ajong was carried out by the Malay community, Sambas Regency had a social role in order to establish relations with human beings, as well as to have a religious role, namely to establish human relations with the Almighty God. Through the tradition of antar ajong, as a cornerstone for religious development in the community also will be created, and closer to a lifestyle that is opt to Islamic guidance, besides antar ajong tradition contains Islamic values. Therefore, Muslim community in its association reveals positive behavior, because it is directed to always do something good, right through ethics and morals in society.